Employee Engagement of Sub-District Administrative Organizations In Thailand - Konsub, Ratchanee; Sangmahachai, Suwannee (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
The purpose of this dissertation is to study: 1. The relationship between transformational leadership, quality of work life and aachievement culture organizational with employee engagement of sub-district administrative organizations. 2. Comparison of the dedication of sub-district administrative organizations classified by size of sub-district administrative organizations. This research was a quantitative research by using a questionnaire. The population is 3,182 employees of sub-district administrative organizations. And the sample size was determined by Taro Yamane’s formula at the confidence level of 90%, the sample group was 285 people. Accidental random sampling collected data for 400 people, the researcher therefore used a group of 400 people. Statistics used to analyze the data were percentage, mean, standard deviation, Correlation Analysis, Multiple regression analysis and t-test. Findings showed that 1) Transformational leadership and achievement culture organizational positive direct relationships with employee engagement at the statistically significant level of .01. 2) The size of sub-district administrative organizations that are different will cause the staff’s dedication in knowledge and thinking with emotional commitment there is a difference. The medium-sized sub-district administrative organization will have a dedication in knowledge and thinking with more emotional dedication than large sub-district administrative organizations. But there was no difference in employee engagement medium and large sub-district administrative organizations. Policy recommendations: expanding knowledge of organizational behavior that correlates with the dedication of employees and executives of sub-district administrative organizations apply research results to develop employees to be dedicated to their work to achieve the highest efficiency and effectiveness for Sub-district Administrative Organizations in Thailand. Article history: Received 2 March 2023 Revised 8 May 2023 Accepted 13 May 2023 SIMILARITY INDEX = 4.13 %